How Continuous Are the “Relict” Landscapes of Southeastern Tibet? - Fox, Matthew; Carter, Andrew; Dai, Jin-Gen (Frontiers in Earth Science, 2020)
Pervasive low-relief, high-elevation surfaces separated by incised canyons are common across the Southeastern margin of the Tibetan Plateau and have been used to define the nature of crustal deformation that drove plateau growth. A common assumption is that these surfaces were once part of a continuous low-relief paleotopography that has undergone surface uplift and dissection. Recent research, however, has questioned this assumption and the derived geodynamic models, which suggests that these surfaces formed in situ through drainage network reorganization and the piracy of upstream drainage area. Here, we test the continuity of the low-relief surfaces across SE Tibet using a new inversion scheme that also illuminates the nature of conflicting hypotheses. Our analysis is based on combining the local information contained in maps of normalized channel steepness with the more distributed and integrated information contained in maps of normalized landscape response time. This allows us to model the formation of a hypothetical landscape prior to rock uplift and dissection. We find that large variations in channel steepness are required along the trunk channels within the inferred paleotopography. This is inconsistent with a low-relief surface prior to surface uplift and indicates that a surface interpolated between remnants cannot be used to robustly measure geodynamic processes in space and time. Furthermore, our inverse framework highlights many different solutions to this ill-posed problem and thus provides an explanation as to why the topography alone cannot be used to provide a unique solution to the debate.